2014
DOI: 10.7785/tcrt.2012.500366
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Infections and Cancer: Implications in Epidemiology

Abstract: Approximately 18% of the global cancer burden has been attributed to infectious agents, with estimates ranging from 7% in developed countries to about 22% in developing countries.Chronic infections caused by the hepatitis B and C viruses, human papilloma viruses (HPV), and Helicobacter pylori (H. pylori) are reported to be responsible for approximately 15% of all human cancers. Interestingly, although many of the infectious agents that have been associated with cancer-such as HPV, Epstein-Barr virus (EBV), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 238 publications
(311 reference statements)
1
41
0
Order By: Relevance
“…Second, other unknown infection(s) may increase the chance of HPV infection. These multiple infections may affect a woman's susceptibility to HPV, or its persistence (17). Lee et al showed that changes in vaginal microbiota in post-menopausal women made them more susceptible to HPV infection (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, other unknown infection(s) may increase the chance of HPV infection. These multiple infections may affect a woman's susceptibility to HPV, or its persistence (17). Lee et al showed that changes in vaginal microbiota in post-menopausal women made them more susceptible to HPV infection (18).…”
Section: Discussionmentioning
confidence: 99%
“…HPV, human papillomavirus. developing cervical cancer (17). However, the interaction of various genotypes in co-infections remains unclear, and future studies are needed to verify whether coordinated mechanisms in co-infections exist.…”
Section: Discussionmentioning
confidence: 99%
“…While the E6 protein of HPV inactivates p53 and E7 inactivates the retinoblastoma (Rb) tumor suppressor protein, detailed studies on a large number of tumors indicate that viral infection alone is not sufficient for tumor development. Studies have also shown that 20 to 30 million Americans are infected with HPV (7). However, only those in a subset develop cervical cancer.…”
mentioning
confidence: 99%
“…To examine the intracellular processing of HPV16 PsV, 4 ϫ 10 5 HaCaT cells/well were plated in 6-well plates overnight and then treated with 2 ng/ml IFN-␥ prior to incubation with PsV. Nine hundred nanograms of PsV, based on L1 protein amount, was added per well and incubated for the indicated time.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the cellular processing of EGFR, 4 ϫ 10 5 HaCaT cells, plated in 12-well plates, were either left untreated or were IFN-␥ treated (2 ng/ml) overnight. Cells were then incubated with 10 mg/ml cycloheximide for 30 min prior to addition of 100 ng of EGF and incubated for the indicated times.…”
Section: Methodsmentioning
confidence: 99%